OPTIMIZATION OF ASPERGILLUS ORYZAE FERMENTATION CONDITIONS FOR KOJIC ACID PRODUCTION - Azzahra, Adnina Fitra; Sukarna, Dyah Karina Puspita; Suryadi, Herman (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study is to obtain the optimal fermentation conditions for Aspergillus oryzae by gradually optimizing the medium and fermentation conditions. Methods: Fermentation condition were optimized by varying carbon and nitrogen sources, pH medium, temperature, and aeration condition. Levels of kojic acid were determined using thin-layer chromatography-densitometry with an ultraviolet detector at a wavelength of 318 nm. Results: A combination of sucrose and yeast extract was chosen as the best source of carbon and nitrogen, respectively, from nine medium variations, producing 1.5425 g/L kojic acid. The optimum acidity of the medium was at pH 4.5, producing 1.7127 g/L of kojic acid, compared with pH 3.5 and 5.5. Compared with fermentation at room temperature, fermentation at 35Â°C yielded greater kojic acid production. The best aeration condition was 100 mL medium in 250 mL flask that produced the most kojic acid (1.6472 g/L). Conclusion: The optimal medium for fermentation of kojic acid using A. oryzae uses sucrose and yeast extract as carbon and nitrogen sources, respectively, at pH 4.5. The optimal aeration and incubation conditions were used, a volume of 100 mL in a 250 mL conical flask, incubated at 35Â°C, obtaining the highest yield value of 0.0370 g/g.